The Changes in Budget Tightening and Emotional Exhaustion: Role Ambiguity as Mediator and Trust as Moderator - Luthfihani, Chindy Anggraeni; Setin, Setin (Jurnal Akuntansi, 2024)
Purpose - This study aims to determine how changes in budget tightness, emotional exhaustion, role ambiguity and trust in senior management after the Covid-19 Pandemic affected the hospitality industry in West Java. Design/methodology/approach - This study uses a quantitative approach with data collection through questionnaires distributed online to 121 hospitality industry managers in West Java. The sample selection was randomized. Findings - The results showed that budget tightness affects role ambiguity, role ambiguity affects emotional exhaustion, trust in senior management strengthens the relationship between budget tightness and role ambiguity. Research limitations/implications - The implication of these findings is that the hospitality industry should prepare for future challenges by strengthening trust between management and employees, reducing role ambiguity through clear communication of job expectations, and managing emotional exhaustion through wellbeing support and management strategies. Limitations of this study include post-pandemic conditions without direct comparison with pre-pandemic conditions. Keywords: Budget Tightness, Emotional Exhaustion, Role Ambiguity, Trust